Determinants of adverse management outcomes of blunt abdominal trauma patients operated at a referral hospital in southern Ethiopia: a retrospective record review - Demoz Abraha; Essay Gebreyes; Eskinder Wolka; Getahun Dender; Abebe Sorsa; Joshua Muhumuza (BMC Surgery, 2023)
Abstract Background Abdominal trauma is one of the common reasons for emergency visits yet there is paucity of data about the subject in the horn of Africa. This study was aimed at determining the determinants of adverse management outcomes of blunt abdominal trauma among operated patients at Wolaita Sodo University Teaching and Referral Hospital, Ethiopia. Methods This was a three-year retrospective review conducted among 128 patient records selected using purposive sampling in which all records for the patients operated for a diagnosis of blunt abdominal trauma during the study period were included. A pretested checklist was used to extract the data relating to adverse outcomes and characteristics of the patients. A descriptive analysis followed by logistic regression was done. Results Of the 128 patients, adverse management outcomes related to blunt abdominal trauma occurred in 52%. Patients residing in rural areas (adjusted odds ratio 3.23, 95% confidence interval: 1.13–9.24) and those with tachycardia, (adjusted odds ratio = 3.25, 95% confidence interval: 1.19–8.83) or tachypnea (adjusted odds ratio 3.25, 95% confidence interval: 1.19–8.83) were more likely to have adverse management outcomes. Conclusion Adverse management outcomes are relatively high and associated with rural residence and deranged vital signs (tachycardia and tachypnea). Close monitoring targeting patients from rural residence and those presenting with tachycardia and tachypnea is recommended.